Carbon sequestration effects of the typical restored vegetation types in Eastern Qinling Mountains - XU Xiaoming; YAN Shanshan; PENG Xiaobang (Xibei zhiwu xuebao)
[Objective] To establish a foundation for addressing climate change and implementing major national ecological projects, this study investigated the carbon sequestration attributes of the representative restored vegetation types within ecologically sensitive regions of Qinling Mountains. [Methods] Seven typical vegetation types [Pinus tabuliformis Carr., Quercus variabilis Blume, P . tabuliformis-Quercus variabilis mixed forests, Platycladus orientalis (L.) Franco, Robinia pseudoacacia L., grassland, and farmland] were selected in eastern Qinling Mountains. The carbon sequestration effects and characteristics of carbon density composition were analyzed through a survey of vegetation communities and calculation of organic carbon in the above-ground vegetations, ground litter, and soil profile across different ecosystem types. [Results] (1) The carbon sequestration function of the typical restored forestlands and grasslands in eastern Qinling Mountains was significant, showing P . orientalis (L.) Franco (16 325.2 g/m2) > Q. variabilis Blume (16 073.0 g/m2) > P . tabuliformis-Q. variabilis mixed forests (11 729.5 g/m2) > R. pseudoacacia L. (9 023.9 g/m2) > P. tabuliformis Carr. (8 610.1 g/m2) > grassland (7 177.9 g/m2) > farmland (5 496.2 g/m2). The forest ecosystem exhibited the highest carbon sequestration effect followed by grassland ecosystem and farmland ecosystem. The composition ratio of ecosystem carbon density was characterized by soil layer > vegetation layer > litter layer. (2) Carbon sequestration capacity was generally increased with restoration years. The carbon density of forest ecosystems was higher in the middle- aged forest stage and near-mature forest stage. Carbon storage began to stabilize and slowly decline in the over-mature forest stage. (3) There were notable differences in carbon density among various restored vegetation types on shaded versus sunny slopes. Furthermore, forest ecosystems displayed more pronounced variations based on slope direction. [Conclusion] These findings indicate that vegetative carbon sequestration is different among different stands, and exhibits phased characteristics correlated with forest age. However, effective management strategies for high-carbon sink tree species tailored to local conditions are essential for achieving national goals for carbon neutrality by 2060.